LITERATUR REVIEW: PEMANFAATAN METABARCODING DNA LINGKUNGAN UNTUK MENGANALISIS KEANEKARAGAMAN HAYATI IKAN - Anggraeni, Diah Arum; Anggraito, Yustinus Ulung; Setiati, Ning (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Environmental DNA (eDNA) metabarcoding is a new method for assessing biodiversity in which samples are taken from the environment via water, sediment or air from which DNA is extracted, and then amplified using common or universal primers in a polymerase chain reaction and sequenced using next-generation DNA. sequencing to produce thousands to millions of sequences. From this data, the presence of species can be determined, and overall biodiversity can be assessed.. Methods: The method used is a literature review using reputable national and international journals Results: Based on the results of the literature review, the use of eDNA metabarcoding can be used to analyze fish biodiversity. eDNA metabarcoding can be analyzed with primary data, databases, and bioinformatic pipelines. Conclusion: eDNA metabarcoding has been widely used to study fish communities in lakes and rivers, as well as coastal fish communities. Despite its considerable ability to detect fish species in large aquatic systems, many methods still need to be understood to improve the quality of primers, databases, and pipelines for analyzing fish biodiversity